2022
DOI: 10.1038/s41598-022-12879-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epitheliotrophic factors in platelet-rich plasma versus autologous serum and their treatment efficacy in dry eye disease

Abstract: Current treatment of severe dry eye disease (DED) includes blood-derived eye drops, such as autologous serum (AS), which lubricate the eyes and provide factors that improve ocular surface and aid in wound healing. Recent studies indicated that platelet-rich plasma (PRP) was also effective. This study aims to compare the concentration and stability of epitheliotrophic factors in AS and PRP and their efficacy in DED patients. Epitheliotrophic factors of interest are epidermal growth factor (EGF), fibronectin, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…APC contains high amounts of coagulation factor, plateletderived growth factor, transforming growth factor-b, insulin like growth factor, and fibroblast growth factor. [19][20][21][22] These factors can stimulate proliferative and differentiation activities, which can improve wound healing through autocrine and paracrine mechanisms and promote MH healing. 15 On the other hand, APC could form platelet-rich fibrin, which can "seal" the MH, prevent fluid turbulence from the vitreous cavity entering the hole, provide a solid scaffold for cell proliferation and migration, and help to restore the central concave structure.…”
Section: Discussionmentioning
confidence: 99%
“…APC contains high amounts of coagulation factor, plateletderived growth factor, transforming growth factor-b, insulin like growth factor, and fibroblast growth factor. [19][20][21][22] These factors can stimulate proliferative and differentiation activities, which can improve wound healing through autocrine and paracrine mechanisms and promote MH healing. 15 On the other hand, APC could form platelet-rich fibrin, which can "seal" the MH, prevent fluid turbulence from the vitreous cavity entering the hole, provide a solid scaffold for cell proliferation and migration, and help to restore the central concave structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, PRP outperformed AS. The studies and the consistent positive outcomes aided in concluding that PRP can be an alternative to AS for the treatment of DED because it demonstrated a shelf life of 3 months when stored at −20 • C [181]. Clinical studies in the field of ophthalmology have also been found to explore the potential of PRP with commendable success while treating DED and corneal epithelial abnormalities [172][173][174].…”
Section: Ophthalmologymentioning
confidence: 99%
“…Allogeneic serum eye drops can also be used for this purpose, and a recent small clinical trial showed comparable efficacy and tolerability as autologous serum tears [8]. Another small clinical trial directly compared autologous serum to platelet-rich plasma, and found no difference in patient preference or clinical results between the formulations, although there were some differences in concentration of epitheliotropic factors [9].…”
Section: Blood-derived Topicalsmentioning
confidence: 99%